Дослідження на Поділлі у 2009 р. - Строцень, Б.С. (Археологічні дослідження в Україні, 2010)
Information on results of the research by the State Enterprise the Protective Archaeological Service of Ukraine of the IA NASU «Podillya Archaeology» during the archaeological examination at the territory of Ternopil and Khmelnytskyi Oblasts.